Kinerja Filter Membran Kitosan-Kulit Udang/PVA Berbasis Karbon Aktif pada Pengolahan Air Siring Sungai Kayan, Kalimantan Utara - Sari, Ayu LIngga Ratna; Sulaiman, Dady; Ulva , Siti Maria (Universitas Islam Negeri Alauddin Makassar, 2025)
Raw water treatment into clean water that meets quality standards is a significant challenge. One method of water treatment is using membrane filtration. In this study, membrane filtration utilized chitosan (shrimp shell) and PVA with activated carbon variations. Activated carbon possesses a large pore structure, allowing various contaminants to be trapped. The membranes were tested for flux and permeability using a dead-end flow system. Meanwhile, the quality of the filtered water was evaluated by measuring TDS and pH. The research results show that the chitosan (shrimp shell) and PVA membranes with activated carbon addition exhibit good performance, as seen from the flux test, permeability test, and membrane performance in water treatment. Specifically, M2, with a 1% activated carbon mixture, demonstrated better flux and permeability values compared to other membrane samples. For M2, flux values of 1.26 L/cm².hr, 5.75 L/cm².hr, and 6.10 L/cm².hr were obtained with increasing pressure applied to the membrane at 0.5, 1, and 1.5 Bar, respectively. It also had a permeability value of 4.11 L/cm².hr.Bar, which is higher than other membranes. Water quality test results also showed good outcomes, indicated by a decrease in pH and TDS values.